Replacing school and out-of-school sedentary behaviors with physical activity and its associations with adiposity in children and adolescents: a compositional isotemporal substitution analysis - Gába, Aleš; Dygrýn, Jan; Štefelová, Nikola; Rubín, Lukáš; Hron, Karel; Jakubec, Lukáš (Environmental health and preventive medicine, 2021)
BACKGROUND: Little is known on how context-specific sedentary behaviors (SB) affect adiposity. This study aimed to investigate compositional associations between context-specific SB and adiposity and estimate the differences in adiposity associated with replacing school and out-of-school SB with physical activity (PA). METHODS: This study included 336 children and adolescents. Time spent in SB and PA was estimated using multi-day 24-hour raw accelerometer data. SB and PA were specified for school and out-of-school times. Fat mass percentage (FM%) and fat mass index (FMI) were used as adiposity indicators. A compositional isotemporal substitution model was used to estimate differences in adiposity associated with one-to-one reallocations of time from context-specific SB to PA. RESULTS: Participants spent approximately two thirds of their school and out-of-school time being sedentary. Relative to the remaining 24-h movement behaviors, significant associations between out-of-school SB and adiposity were found in both boys (βilr1 = 0.63, 95% confidence interval [CI] = 0.03-1.22 for FM%; βilr1 = 0.76, 95% CI = 0.03-1.49 for FMI) and girls (βilr1 = 0.62, 95% CI = 0.25-0.98 for FM%; βilr1 = 0.80, 95% CI = 0.28-1.32 for FMI). Replacing 30 min/day of out-of-school SB with out-of-school light PA decreased FM% by 10.1% (95% CI = 3.3-17.9) and FMI by 14% (95% CI = 2.7-24) in girls. No significant associations were found for school SB. CONCLUSIONS: A reduction of out-of-school SB in favor of light PA should be advocated as an appropriate target for interventions and strategies to prevent childhood obesity.
Keywords: Male; sedavý životní styl; adipozita; Schools; Sedentary Behavior; Humans; Czech Republic; Česká republika; mužské pohlaví; Exercise; Female; mladiství; akcelerometrie; Time-use epidemiology; ženské pohlaví; Adiposity; Compositional data analysis; školy; cvičení; Adolescent; lidé; dítě; Accelerometry; Child